The Contribution of Arm Muscle Strength and Limb Muscle Explosive Power to the 50 Meter Butterfly Swim - Rival, Arivaldy; doni, doni; argantos, argantos; setiawan, yogi; Yendrizal, Yendrizal (Jurnal Gladiator, 2023)
The purpose of writing this article is to determine the contribution of arm muscle strength and leg muscle explosive power to the 50 meter butterfly stroke swimming ability of Specialized Swimming Students, FIK UNP Training Department. This type of research is correlational research. This research was conducted in May 2021 at the FIK UNP Padang swimming pool. In writing this article a sample of 20 students. The instrument in this study used 1) medical ball throwing, 2) standing broad jump test and 3) the 50 meter butterfly swimming test. The analysis technique used simple correlation analysis and multiple correlations. Data analysis showed that: 1) Arm muscle strength contributed 78.09% to the 50 Meter Butterfly Swimming Ability. 2) The explosive power of the leg muscles contributes to the 50 Meter Butterfly Swim Ability by 25.50%, 3) The arm muscle strength and the leg muscle explosive power contribute together to the 50 Meter Butterfly Swim Ability by 78.50 %. Keywords: Arm Muscle Strength, Limb Muscle Explosive Power, 50 meter swimming butterfly power